Seed Viability and Potential Germination Rate of Nine Endemic Boswellia Taxa (Burseraceae) from Socotra Island (Yemen) - Salem Hamdiah; Lukáš Karas; Kateřina Houšková; Kay Van Damme; Fabio Attorre; Petr Vahalík; Hana Habrová; Samuel Lvončík; Klemen Eler; Petr Maděra (Plants, 2022)
The endemic Boswellia species (Burseraceae) on Socotra Island (Yemen) are of great local significance due to their various local ethnobotanical uses. However, despite the fact that these trees are endangered, little is known about their biology. We tested seed germination rates in controlled experiments (trials of 21 days) for two subsequent years and for nine endemic taxa of Boswellia occurring on Socotra Island. For this, seeds were collected island-wide from a wide range of localities and for several populations per species. We observed differences in germination among Boswellia species, among species and localities and among both years, which indicates that the development of seeds is strongly affected by external ecological factors. Although we noted a large variation in seed germination (relatively high in Boswellia socotrana), and half of the species showed relatively low mean daily germination, our study indicated that all endangered endemic Frankincense Tree taxa of Socotra harbor the potential for in situ conservation through recruitment, given that known impacts can be reduced in local replantation areas (e.g., grazing).